2015
DOI: 10.1515/geo-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed paleomagnetic map of the EasternmostMediterranean joined with tectono-structural analysis unmaskgeodynamic history of this region

Abstract: Newly developed paleomagnetic map of the Easternmost Mediterranean joined with tectono-structural analysis unmask geodynamic history of this regionAbstract: Comprehensive magnetic-paleomagnetic analysis of physical-geological models developed for the Easternmost Mediterranean (northern part of the Sinai plate) accompanied by gravity and seismic data examination enabled the detection of a zone of inverse magnetization of submeridional strike with a total volume exceeding 120,000 km . Such a large zone must corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…Gvirtzman et al [53] suggested that the formations composing this graben have a predominantly continental genesis, including soils and coal. According to other data [82,83], the Asher Volcanics relate to a deep basin with a possible ocean-like crust; the results of our investigation [22,31,32] partially agree with the last proposition.…”
Section: Paleomagnetic Maps Of Carmel and Atlit Areassupporting
confidence: 91%
See 4 more Smart Citations
“…Gvirtzman et al [53] suggested that the formations composing this graben have a predominantly continental genesis, including soils and coal. According to other data [82,83], the Asher Volcanics relate to a deep basin with a possible ocean-like crust; the results of our investigation [22,31,32] partially agree with the last proposition.…”
Section: Paleomagnetic Maps Of Carmel and Atlit Areassupporting
confidence: 91%
“…However, their initial application in the easternmost Mediterranean region was triggered by the work of Ben-Avraham et al [30]. The previous experience of our studies in this region [16,18,[31][32][33] indicates that paleomagnetic studies are effective in analyzing the geodynamic-tectonic features of the easternmost Mediterranean.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations